2004
DOI: 10.4049/jimmunol.173.4.2373
|View full text |Cite
|
Sign up to set email alerts
|

Activation through Cannabinoid Receptors 1 and 2 on Dendritic Cells Triggers NF-κB-Dependent Apoptosis: Novel Role for Endogenous and Exogenous Cannabinoids in Immunoregulation

Abstract: The precise role of cannabinoid receptors (CB)1 and CB2, as well as endogenous ligands for these receptors, on immune cells remains unclear. In the current study, we examined the effect of endogenous and exogenous cannabinoids on murine bone marrow-derived dendritic cells (DCs). Addition of Δ9-tetrahydrocannabinol (THC), a major psychoactive component found in marijuana or anandamide, an endogenous cannabinoid, to DC cultures induced apoptosis in DCs. DCs expressed CB1 and CB2 receptors and the engagement of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
148
3
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 182 publications
(163 citation statements)
references
References 56 publications
11
148
3
1
Order By: Relevance
“…To this end, we demonstrated that administration of THC into mice caused a reduction in the cellularity of the thymus and spleen, and decreases the ability of T and B cells to divide upon activation, which correlated with induction of apoptosis [16]. Furthermore, a recent study from our laboratory demonstrated that THC or anandamide, an endogenous cannabinoid, can induce apoptosis in dendritic cells (DCs) in vitro and treatment of mice with THC caused depletion of splenic DCs [13]. While such studies on one hand suggest that abuse of marijuana or clinical use of THC in AIDS or cancer patients may cause an undesired effect namely immunosuppression.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…To this end, we demonstrated that administration of THC into mice caused a reduction in the cellularity of the thymus and spleen, and decreases the ability of T and B cells to divide upon activation, which correlated with induction of apoptosis [16]. Furthermore, a recent study from our laboratory demonstrated that THC or anandamide, an endogenous cannabinoid, can induce apoptosis in dendritic cells (DCs) in vitro and treatment of mice with THC caused depletion of splenic DCs [13]. While such studies on one hand suggest that abuse of marijuana or clinical use of THC in AIDS or cancer patients may cause an undesired effect namely immunosuppression.…”
Section: Introductionmentioning
confidence: 97%
“…Δ 9 -tetrahydrocannabinol (THC), the major psychoactive component of marijuana, and other cannabinoids have been shown to be immunosuppressive both in vitro and in vivo, affecting macrophages, natural killer cells, B cells, T cells, mast cells and dendritic cells (DCs) [1,13,14]. It is generally believed that cannabinoids alter the immune functions through their ability to mediate an effect on cytokine production and to exert anti-proliferative properties [15] (Review).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that THC can modulate the functions of immune cells (7). More recently, we reported that the immunosuppressive property of THC can be attributed, at least in part, to its ability to induce apoptosis in T cells and dendritic cells through ligation of CB2 receptors and that the latter was regulated by activation of nuclear factor-nB (8), recruiting both intrinsic and extrinsic pathways of apoptosis. Interestingly, we also found that THC and other cannabinoids could induce apoptosis in transformed murine and human T cells (9), including primary acute lymphoblastic human leukemia cells, and furthermore that the treatment of mice bearing a T-cell leukemia with THC could cure f25% of the mice (10).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cannabinoid system exerts a control function over the immune system. Activation of CB2 and probably also CB1 receptor, enhances migration and adhesion of immune cells, decreases the release of proinflammatory cytokines (22), and induces apoptosis in dendritic cells (23). These data led to the assumption that endocannabinoid signaling plays a role in the development of neurodegenerative diseases (24) and could be a potential target for novel pharmacotherapies (25).…”
mentioning
confidence: 99%